Local Wisdom and Political Communication in Indonesia: A Systematic Literature Review on Cultural Transformation in the 2024 Electoral Campaigns - Abdul Rahman HI (Nusantara Society Lab, 2026)
This study examines the use of local wisdom in Indonesian political communication as a form of cultural transformation in the 2024 electoral campaigns. The study aims to analyze the integration of local values into contemporary political communication strategies and the factors contributing to their effectiveness. This research employs a systematic literature review (SLR) method by analyzing various studies related to political communication, local culture, and digital campaigns in Indonesia. The findings indicate that the use of local cultural symbols such as wayang performances, traditional clothing, cultural rituals, and religious leadership strengthens campaign resonance, builds emotional connections with communities, and enhances candidates’ political legitimacy. The effectiveness of these strategies is further amplified through the integration of digital media, particularly in engaging young voters. The study also reveals that cultural relevance, the social legitimacy of local leaders, institutional support, and the digital adaptation of cultural symbols are key factors in the success of local wisdom-based political communication. This study concludes that the integration of local traditions and digital media can strengthen inclusive democratic practices while preserving Indonesian cultural identity within contemporary political communication.